Findings in the field of strategy formulation process (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the importance of strategic factors arising from a level of the company policy as well as the level of the strategic management?Purpose: The purpose of this research was to examine selected strategic factors and to determine importance of selected factors in strategy formulation process.Method: We made qualitative research, namely the study of a scientific literature. The emphasis is on research by foreign authors.Results: We found out which strategic factors are important in strategy formulation process. Authors attach great emphasis on factor strengths and weaknesses and also opportunities and threats of the company. Other important factors cited by the authors are the internal and external participants of the company, credibility, competitiveness, entrepreneurship, synergy, culture, philosophy, ethics, ecology and efficiency.Organization: Research is useful both, for future researches as well as practice (for top managers). In the field of strategy formulation process it is impossible to found research that is related on importance of strategic factors in strategy formulation process. The present research will be important tool in strategy formulation process.Society: The research refers to culture, ethics, values and company environment. Selected factors refers to the society, social responsibility and environment. We are explore the importance of the selected factors in strategy formulation process.Originality: Originality of the research is reflected in wide spectrum of strategic factors in the field of strategy planning. We did not find any research that considers such a wide spectrum of strategic factors.Limitations/Future Research: We restricted ourselves on strategic factors that derives from a level of the company policy and strategic management and on researches that has already been made. A suggestion for further research is quantitative research that will examine selected strategic factors and try to explain their influence on strategy formulation process.
Keywords: strategic factors; strategy planning; strategic management; strategy formulation process; company policy; management